Design and analysis of an ergonomic portable lifting device / Muhammad Fahmi Mohd Jais - Mohd Jais, Muhammad Fahmi (2023)
The portable lifting device is inspired by the principle of the lever Lifting devices are designed to hoist, lower, and transport heavy pieces of machinery, equipment, or other materials around a given workstation. As such, using a portable lifting device enables more fluid, streamlined movement. Instead of having one or more employees shift heavy weight between them and potentially fumble the item being carried, a designated device can easily move items from one location to the next at the touch of a button. The objective of creating this product is to save labour and time. In addition, the portable lifting device also has innovations on the wheelbase, 4 rubber wheels were added to the base to give a smooth movement. The portable lifting device design is suitable for all types of material because our project can be adjusted according to the size of the material to be moved. The research rate obtained from the survey stated that is difficult to move heavy furniture abed it required two people or more. Most respondents agree that a "portable lifting device" is suitable to use at home, warehouses and in factories.